E-Book Core Stability Exercise on Myogenic Low Back Pain - Wanti Hasmar; Faridah (Formosa Publisher, 2022)
Myogenic low back pain is pain related to stress or strain on the back muscles, tendons and ligaments which are usually present when you do excessive daily activities. Low back pain needs to get attention because it can become a problem such as lost work time, reducing work productivity. This research is a quasi-experimental study with a one group pre-test post-test design. The sample in this study amounted to 10 people. The sampling technique is by means of proportional stratified random sampling. The results showed that after carrying out core stability using a control sheet, it had not made positive changes for batik craftsmen who experienced myogenic lower back pain.